Informality and rural industry: Rethinking the impacts of E-Commerce on rural development in China - Tang, Weicheng; Zhu, Jin (Journal of rural studies, 2020)
The adoption and diffusion of e-commerce in developing countries exerts a fundamental influence on economic growth and on people’s daily lives. The impacts of diffuse e-commerce platforms on rural China are exemplified by the sharp increase in the number of ‘Taobao villages’. The Taobao village is regarded as an effective means of revitalising rural areas and narrowing the rural–urban gap by both academia and the government. However, our case study in Zeguo Town, Zhejiang Province demonstrates that such an attitude seems over-optimistic. Supported by document review and semi-structured interviews with local government officials, village cadres and entrepreneurs of leading enterprises and also small and medium-sized workshops, our study reveals that the rapid growth of the local footwear industry in Zeguo Town is an outcome of the lowered capital barriers for entry brought through Taobao. In response to this rapid growth, migrants have flooded into the local industry and started their own businesses. As a result, the cost of production elements such as industrial land and labour rose significantly, threatening the survival of cost-sensitive enterprises. As rational economic subjects, entrepreneurs’ pursuit of low-cost spaces and local farmers’ provision of vacant houses to entrepreneurs contributed to an e-commerce-induced informality. Many small and medium-sized shoemaking workshops and Taobao online shops penetrated surrounding rural villages. E-commerce-induced informality not only challenged rural governance but also undermined the operation of leading enterprises as new small enterprises disrupt the pricing of products, labour costs and even affect the reputation of local industry. The current unregulated development and seemingly rapid growth only store up troubles in the future. •The ‘Taobao village’ is regarded as an effective means of revitalising rural areas and narrowing the urban–rural gap.•E-commerce boom in China has led to the rapid growth of the local footwear industry but also contributes to rising costs of production elements.•Pursuit of low-cost spaces by entrepreneurs and provision of vacant houses by local farmers has encouraged an e-commence-induced informality.•Leading enterprises have been disadvantaged as the small ones disrupt product pricing, labour cost and even alter the reputation of local industry.•E-commerce-induced informality also brings about a series of challenges to rural governance.